Interuniversity Microelectronics Center (IMEC) (B) - Chesbrough, Henry William, (SAGE Knowledge. Cases., 2017)
The IMEC case study allows students to discuss open innovation in the context of research organizations with industry partnerships. Johan Van Helleputte, the Vice President of Strategic Management at Interuniversity Microelectrics Center (IMEC), a European research institute that focuses on advanced microelectronics research for applications in the semiconductor industry, is on the verge of presenting a growth strategy to his Board for approval. With the assistance of his team, Val Helleputte had discussed whether to develop an advanced 300 mm wafer research laboratory that would require an investment of more than $1 billion. If a decision were made to go through with this investment, three primary challenges would need to be met: 1) raising the necessary capital to fund the investment, 2) managing the intellectual property arising from the project, and 3) engaging IMECs industry partners in the project.